PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN TOUR & TRAVEL DI KOTA PONTIANAK - Angelina Fitria Rina Sari (Jurnal Ekonomi Integra, 2020)
Human resources are assets that are very important for the organization or company so the company must be able to develop human resources properly to assist the company in achieving its objectives in accordance with the specified targets. With good human resources, it is expected that companies will be able to optimize and improve the performance of employees. To improve and optimize the performance of employees, companies need to make efforts, such as providing work motivation and employee job satisfaction. This study wants to prove the effect of each variable, namely motivation and job satisfaction on the performance of Tour & Travel employees in Pontianak. Based on previous research and linked to supporting theories put forward by experts using the SPSS 21 program as a statistical data processing tool. This type of research is associative research. The population in the study was 112 employees taken from 21 Tour & Travel companies in Pontianak City and the entire population was sampled with data analysis techniques using multiple linear regression analysis. The results of this study indicate that motivation and job satisfaction significantly influence employee performance.